Peptide Amphiphiles for Pharmaceutical Applications - Fuertes-Llanos, Mayra A.; Gómara, Maria José; Haro, Isabel; Sánchez-López, Elena (Current Medicinal Chemistry, 2024)
During the last few decades, several efforts have been made towards developing biocompatible materials. Among them, peptide amphiphiles (PAs) constitute a novel nanotechnological strategy used in the field of biomedicine since they can provide tissue- specific binding and localization. PAs possess several regions combining hydrophobic and hydrophilic areas that are able to self-assemble in aqueous media, forming different tertiary nanostructures able to interact with cellular membranes. Moreover, these molecules can be tuned by incorporating collagen, lipids, or fluorescent markers. In addition, they can also be used as carriers in order to encapsulate active compounds for drug delivery showing promising features in this area. In this review, the self-assembled structures of PAs as well as their pharmacological applications have been summarized. Furthermore, their use as drug delivery systems has been highlighted and the latest advances in this field have been reviewed.
Keywords: anticancer